CARIES OF THE EARLY IRON CENTURYPOPULATION OF POLTAVA AND CORRELATED AREAS AS REFLECTION ASPECTSOF SOCIAL LIFE - L. F. Kaskova; L. F. Chupryna; N. A. Morhun; M. V. Polesskyi; A. V. Artemiev (Український стоматологічний альманах, 2019)
An attempt has been made to display a picture of carious pathology and other dental diseases based on the study of the general status and reconstruction of cultural and everyday traditions of the early Iron Age society of Poltava and adjacent regions of Ukraine for introduction into the scientific base with the interaction of the formula: disease - social conditions, for a particular territory, specific society, one historical time. The materials of the study were the skeletons of 223 individuals with preserved dental-maxillary area (discovered and collected during the archaeological excavations of mounds 1998–2017 by expeditions of the Center for the Preservation and Research of Monuments of Archeology of the Department of Culture of the Poltava Regional State Administration) of the early Iron Age (mid-5th-6th centuries). BC, hereinafter - RHW) of the territory of Poltava and adjacent areas: 40 skeletons of children, 79 - women, 104 - men. In the analysis of pathology, we used our own method of studying the bones of ancient people and studying the pathology on anthropological material. Studied age-related changes in the skeleton, social labeling (if possible, determined the type of occupation, special social characteristics - decoration of the teeth, effects on the teeth when initiating into adult life, technical use of the masticatory organs, etc.). The social portrait of society shows the clinical picture of caries, other deviations from the generally accepted norm, which can be used as a starting point when comparing caries indicators to earlier or later communities with their social characteristics and economic structure. So, a pathology change curve can be created, with the creation of an intermediate picture of the disease and prediction at any time in the future. Having such a formula of pathological processes in a given population in a given territory at a given time with a given social characteristic, we can further obtain information on the pathology of close and distant communities, which will provide new methods for dating and recreating life. For medicine, it is important to trace causal relationships. It is, therefore, possible to derive diagrams of diseases at the level of similar conditions of life and management (expect a similar status of the oral cavity in similar societies).